Exercise and Fat Metabolism: Solutions to a Long-Standing Conundrum. (May 2022) - Leslie, Eric; Mermier, Christine; Kravitz, Len
Abstract : Fat metabolism is a fundamental, metabolic process for energy production. Evidence shows that several types of aerobic- and resistance-based exercise not only promote fat burning but also improve the mechanisms for how our body burns fat, which leads to greater health and fitness. Apply It!: Several types of exercise promote fat burning, which provides flexibility in exercise prescription to achieve benefits in fat metabolism. Individualized exercise prescription, with any type of exercise, promotes exercise adherence and optimizes the training-related benefits in fat metabolism.